2021
DOI: 10.1016/j.cegh.2021.100872
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and health-related quality of life with short form-36 for multidrug-resistant tuberculosis patients in Jambi, Indonesia: A case-control study

Abstract: Background: Multidrug-resistant tuberculosis (MDR-TB) is another problem in TB elimination. In 2018, 484,000 people worldwide developed tuberculosis that was resistant to rifampicin, and 78% of those had MDR-TB. Estimation of risk factors to detect MDR-TB. Methods: A case-control study assesses the estimate of the socio-demographic, house environment, diabetes mellitus, treatment behavior, and health-related quality of life (HRQOL). There were 28 cases of MDR-TB patients, and 56 control of drug-susceptible tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Joint pain is a reported side effect of second‐line TB drugs, including bedaquiline [25]; however, other studies using the SF‐36 found that pain was less significant in the MDR‐TB group [26] than in the DS‐TB group. At the same time, patients included in our study reported better quality of life outcomes than patients in other studies, especially concerning DR‐TB [7, 26–29]. As in our study, other research showed improvement in quality of life after the completion of TB treatment, especially visible on the EQ‐5D‐5L general health visual analogue scale.…”
Section: Discussionsupporting
confidence: 78%
“…Joint pain is a reported side effect of second‐line TB drugs, including bedaquiline [25]; however, other studies using the SF‐36 found that pain was less significant in the MDR‐TB group [26] than in the DS‐TB group. At the same time, patients included in our study reported better quality of life outcomes than patients in other studies, especially concerning DR‐TB [7, 26–29]. As in our study, other research showed improvement in quality of life after the completion of TB treatment, especially visible on the EQ‐5D‐5L general health visual analogue scale.…”
Section: Discussionsupporting
confidence: 78%
“…Female patients are the most neglected population in society, possibly due to the high levels of stigma and discrimination against them in Pakistan ( Habib et al, 2021 ). As a result, gender is an important social predictor of health, and inequalities in gender-related HRQoL parameters must be considered ( Izhar et al, 2021 ). In this study, in the control group, smoking was identified to interact with the trend of the HRQoL of TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Risiko penyakit tuberkulosis untuk kelompok dengan status ekonomi di bawah upah minimum adalah 7,667 kali lebih berisiko dibandingkan kelompok dengan status ekonomi di atas upah minimum (Sejati & Hidayanti, 2020). Riwayat diabetes dengan kejadian tuberkulosis memiliki hubungan yang bermakna sebesar 3,45 kali (Izhar, Butar, Hidayati, & Ruwayda, 2021). Variabel riwayat kontak keluarga serumah dengan kejadian tuberkulosis paru menunjukkan hubungan statistik antara riwayat kontak keluarga serumah dengan kejadian tuberkulosis paru dengan nilai OR 3,50 (Alnur & Pangestika, 2018).…”
Section: Pendahuluanunclassified